Pengaruh Kualitas Audit, Earning Per Share, Price to Book Value dan Islamic Social Reporting Terhadap Return Saham Pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di ISSI Tahun 2018-2023 - Moh. Syahdan Irjan Sidiq; Titin Agustin Nengsih; Khairiyani Khairiyani (LPPM Universitas Sains dan Teknologi Komputer, 2026)
Stock returns are an indicator of investment returns that reflect the profits or losses incurred by investors over a specific period. This study aims to analyze the effect of Audit Quality, Earnings Per Share (EPS), Price to Book Value (PBV), and Islamic Social Reporting (ISR) on stock returns, both collectively and individually. The research focuses on food and beverage sub-sector companies listed on the Indonesian Sharia Stock Index (ISSI) during the 2018–2023 period. The method used in this study is a descriptive quantitative approach utilizing secondary data. The population and sample consisted of 11 food and beverage sub-sector companies listed on the ISSI. Data collection was conducted through documentation techniques, while data analysis used panel data regression. The results show that Audit Quality, EPS, PBV, and ISR simultaneously influence stock returns. Partially, the variables Price to Book Value and Islamic Social Reporting were shown to have a significant influence on stock returns, while Audit Quality and Earnings Per Share did not. Based on the coefficient of determination value, it is known that the independent variables in this study are able to explain the variation in stock returns by 87.51%, while the remainder is influenced by other factors outside the research model